The effect of intermittent fasting on microbiota as a therapeutic approach in obesity - Cadena-Ullauri, Santiago; Guevara-Ramírez, Patricia; Ruiz-Pozo, Viviana A.; Tamayo-Trujillo, Rafael; Paz-Cruz, Elius; Zambrano-Villacres, Rayner; Simancas-Racines, Daniel; Zambrano, Ana Karina (Frontiers in Nutrition, 2024)
Obesity, a public health challenge, arises from a complex interplay of factors such as dietary habits and genetic predisposition. Alterations in gut microbiota, characterized by an imbalance between Firmicutes and Bacteroidetes, further exacerbate metabolic dysregulation, promoting inflammation and metabolic disturbances. Intermittent fasting (IF) emerges as a promising dietary strategy showing efficacy in weight management and favoring fat utilization. Studies have used mice as animal models to demonstrate the impact of IF on gut microbiota composition, highlighting enhanced metabolism and reduced inflammation. In humans, preliminary evidence suggests that IF promotes a healthy microbiota profile, with increased richness and abundance of beneficial bacterial strains like Lactobacillus and Akkermansia. However, further clinical trials are necessary to validate these findings and elucidate the long-term effects of IF on microbiota and obesity. Future research should focus on specific tissues and cells, the use of advanced -omics techniques, and exploring the interaction of IF with other dietary patterns, to analyze microbiota composition, gene expression, and potential synergistic effects for enhanced metabolic health. While preliminary evidence supports the potential benefits of IF in obesity management and microbiota regulation, further research with diverse populations and robust methodologies is necessary to understand its implications and optimize personalized dietary interventions.This review explores the potential impact of IF on gut microbiota and its intricate relationship with obesity. Specifically, we will focus on elucidating the underlying mechanisms through which IF affects microbiota composition, as well as its subsequent effects on obesity.